MANAJEMEN KEBIDANAN KOMPREHENSIF PRIMIGRAVIDA DENGAN ZTATUS GIZI KURANG DI MASA PANDEMI COVID-19 - Yuliana Fransiska Dapa Yuliana Fransiska Dapa (Media Husada Journal Of Nursing Science, 2021)
According to the IDHS, the MMR in 2018 has decreased but is still quite high. The high MMR indicates that the health status in Indonesia is still not good. One of the factors causing AKI and IMR is pregnancy in mothers with poor nutritional status. Poor nutritional status will cause babies to be born with LBW so that the potential for death is higher. Efforts and steps for handling this strategy are to carry out comprehensive midwifery care for mothers starting from pregnancy, childbirth, postpartum, newborns and family planning (KB). Appropriate care related to the fulfillment of nutrition for pregnant women will have a positive impact on the delivery process, postpartum and BBL. The aim is to provide comprehensive care and to observe the results of the process of pregnancy, childbirth, postpartum, low birth weight and family planning to mothers with poor nutritional status. The case study uses a descriptive observational method. The study was carried out at PMB Ngadillah Asrikaton Pakis with the subject of the case study being Mrs. A, carried out from March to July 2021. The results showed that pregnancy had problems with poor nutritional status (BMI <18), but pregnancy progressed normally, increasing maternal weight during pregnancy. pregnant is 15 kg. The delivery took place normally vaginally with the duration of the 1st stage being 6 hours, the baby was born 12 minutes after complete dilatation, the placenta was born complete with approximately 6 minutes and 2nd degree laceration. The involution was normal, the baby was healthy and given exclusive breastfeeding. Infants are not given formula milk or other complementary foods. Injectable contraception is the choice of contraception, there are side effects of weight loss due to disruption of rest patterns. It can be concluded that comprehensive midwifery care has a positive impact on pregnancy with poor nutritional status by optimizing appropriate intake and nutrition.